Clinical outcomes of dose-escalated re-irradiation in patients with recurrent high-grade glioma. Issue 5 (2nd May 2022) - Helis, Corbin A; Prim, Shih-Ni; Cramer, Christina K; Strowd, Roy; Lesser, Glenn J; White, Jaclyn J; Tatter, Stephen B; Laxton, Adrian W; Whitlow, Christopher; Lo, Hui-Wen; Debinski, Waldemar; Ververs, James D; et al.
Abstract: Background: Re-irradiation for recurrent gliomas is a controversial treatment option with no clear standard dose or concurrent systemic therapy. Methods: This series represents a single-institution retrospective review of patients treated with re-irradiation for recurrent high-grade glioma. After 2012, patients were commonly offered concurrent bevacizumab as a cytoprotective agent against radiation necrosis. Kaplan-Meier method was used to estimate overall survival and progression-free survival. Cox proportional hazards regression was used to identify factors associated with overall survival and progression-free survival. Results: Between 2001 and 2021, 52 patients underwent re-irradiation for a diagnosis of recurrent high-grade glioma. 36 patients (69.2%) had a histologic diagnosis of glioblastoma at the time of re-irradiation. The median BED10 (biological equivalent dose 10 Gy) of re-irradiation was 53.1 Gy. Twenty-one patients (40.4%) received concurrent bevacizumab with re-irradiation. Median survival for the entire cohort and for glioblastoma at the time of recurrence patients was 6.7 months and 6.0 months, respectively. For patients with glioblastoma at the time of recurrence, completing re-irradiation (HR 0.03, P < .001), use of concurrent bevacizumab (HR 0.3, P = .009), and the BED10 (HR 0.9, P = .005) were predictive of overall survival. Nine patients developed grade 3-5 toxicity; of these, 2 received concurrent bevacizumab and 7 did not ( P = .15). Conclusion: High dose re-irradiation with concurrent bevacizumab is feasible in patients with recurrent gliomas. Concurrent bevacizumab and increasing radiation dose may improve survival in patients with recurrent glioblastoma.